Rickettsiosis, una enfermedad letal emergente y re-emergente en Colombia - Juan David Rodas González (Universitas Scientiarum)
Rickettsiosis: a deadly emerging and re-emerging disease in Colombia. Rickettsiosis was first described in Colombia in 1937 byDr Luis Patiño during an outbreak of a disease with unspecific signs. Rickettsia is a genus of Gram-negative intracellular obligatorybacteria having caused several epidemics around the world, and are transmitted mainly by ticks, fleas, lice and mites. The most fatalwithin this group of diseases is known as Rocky Mountain Spotted Fever (RMSF), which is caused by Rickettsia rickettsia. There is alsothe endemic typhus caused by Rickettsia typhi and epidemic typhus caused by Rickettsia prowazekii. In Colombia, several outbreaks ofRMSF have occurred during the last decade. The best known among those have hit the municipalities of Necoclí and Turbo, in Antioquiain 2006 and 2008 respectively, and Los Cordobas in the department of Cordoba in 2007. The goal of this review is to describe the state ofthe art of rickettsiosis, a forgotten lethal disease that has re-emerged in our country, and leave some questions as an inspiration for future research that will hopefully lead scientists to a better understanding of this entity potentially endemic in some areas of Colombia.